2003
DOI: 10.1897/02-627
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of acidic and neutral drugs in surface waters near sewage treatment plants in the lower Great Lakes, Canada

Abstract: Prescription and nonprescription drugs have been detected in rivers and streams in Europe and the United States. Sewage treatment plants (STPs) are an important source of these contaminants, but few data exist on the spatial distribution of drugs in surface waters near STPs. Samples of surface water were collected in the summer and fall of 2000 at open-water sites in the lower Great Lakes (Lake Ontario and Lake Erie), at sites near the two STPs for the city of Windsor (ON, Canada), and at sites in Hamilton Har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
316
3
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(351 citation statements)
references
References 21 publications
21
316
3
11
Order By: Relevance
“…Ternes, 1998;Ollers et al, 2001, Falås et al, 2012, surface waters (e.g. Ternes, 1998, Metcalfe et al, 2003Andreozzi et al, 2003), and drinking waters (e.g. Stackelberg et al, 2004Stackelberg et al, , 2007Togola and Budzinski, 2008;Heberer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ternes, 1998;Ollers et al, 2001, Falås et al, 2012, surface waters (e.g. Ternes, 1998, Metcalfe et al, 2003Andreozzi et al, 2003), and drinking waters (e.g. Stackelberg et al, 2004Stackelberg et al, , 2007Togola and Budzinski, 2008;Heberer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The main photosensitizers are chromophoric dissolved organic matter (CDOM), nitrate, nitrite, and possibly also H 2 O 2 and Fe compounds. The most important photogenerated transients are • OH, CO 3 −• , 1 O 2 and the triplet states of CDOM, 3 CDOM*. 9 Irradiated CDOM yields 3 CDOM*, 1 O 2 and • OH, [10][11][12][13] the latter also produced by nitrate and nitrite.…”
Section: Introductionmentioning
confidence: 99%
“…Kolpin et al (2002) sampled 139 stream sites in the United States and reported a median detection caffeine concentration of 0.1 lg/L. Metcalfe et al (2003) used caffeine as a marker for human excrement and reported the highest mean caffeine concentration from five Ontario (Canada) sewage-treatment plant (STP) effluents to be 0.677 lg/L. Studies by Thomas and Foster (2005) and Batt et al (2006) examined STP effluents in Virginia and New York, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the monitored effects of pesticides on nontarget organisms in aquatic receiving systems, pharmaceutical compounds' presence in rivers and streams has produced increased scrutiny on their potential ecotoxicologic effects (Maul et al 2006). Several studies have reported the presence of caffeine in surface and ground waters across the world (Weigel et al 2002;Buerge et al 2003;Metcalfe et al 2003;Weigel et al 2004;Sankararamakrishnan & Guo 2005;Thomas & Foster 2005). A study by Kolpin et al (2002) of 139 stream sites in the United States evaluated the occurrence of 95 different OWCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation